Isolation and Antibiotic Sensitivity Testing of Pseudomonas aeruginosa Isolates from Patients with Chronic Suppurative Otitis Media in Baghdad - Fatima Rheem Wadi; Maryam Kareem Ali (Ibn Al-Haitham Journal for Pure and Applied Sciences)
Otitis media is one of the most common types of ear infections, plus bacteria are to blame. Pseudomonas aeruginosa is the most frequently diagnosed pathogen causing this infection. P. aeruginosa has virulence factors that lead to damage to the middle ear mucosa. This study was conducted to identify Pseudomonas aeruginosa causing chronic suppurative otitis media and to determine its antibiotic sensitivity. A total of (100) ear swabs were collected from patients suffering from otitis media attending the ENT outpatient clinic at Baghdad Teaching Hospital from July 2022 till the end of December 2022. Age range was (18-75) years. Identification of bacteria and biochemical testing and antibiotic sensitivity test  of the bacteria spp. were detection of  18 antibiotics for different types were carried out using the VITEK 2 automated system. The study showed the results as follows: Eighty positive cases, distributed among 32 (40%) males and 48 (60%) females. About 25% of patients are between 48-57 years old and 58-67 years old, respectively. A total of 55 patients (68.75%) were from urban areas, and 25 patients (31.25%) were from rural areas .With regard to the antibiotic susceptibility profile, the data showed that the most effective antibiotics were colistin(77%) Ceftazidime(55%) ,Cefepime(45%), Imipenem (42%),   highest resistance percentages of strains to tested antibiotics was for Ceftoriaxone  , Cefpodoxime (100%) and the lowest resistant percentages was (22.5%) for colistin Females were more likely to develop otitis media, and the prevalence appeared to be higher among the elderly. Pseudomonas aeruginosa represents the most implicated bacterial pathogen associated with this infection. colistin is the most effective antibiotic and can be considered as the drug of choice against  P. aeruginosa.